ANALISIS TAWHIDI STRING RELATION (TSR) TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN PEMBIAYAAN PERBANKAN SYARIAH INDONESIA 2009-2019 - Warto A.S; R Bambang Budhijana (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This study uses the Sharia Commercial Bank and Sharia Business Unit as a whole as the object of research from the period 2009-2019 (quarterly). The analysis technique used is multiple linear regression. To find out the relation process used Tawhidi String Relation (TSR) analysis based on unity, correlation and evolution. Based on the research, the results show that Third Party Funds (TPF) have a positive and significant effect on the distribution of Islamic Banking financing. Non Performing Financing (NPF) has a positive and not significant effect on the distribution of bank financing. While Bank Indonesia Sharia Certificates (BISC) have a negative and significant effect on the distribution of bank financing. Based on the TSR analysis, it was concluded that BISC had a negative effect on all variables used in this study, both: DF, TPF and NPF. Therefore, this research can be a criticism for the Islamic banking industry in channeling financing in the form of BISC.